2011
DOI: 10.1111/j.1600-051x.2011.01759.x
|View full text |Cite
|
Sign up to set email alerts
|

A follow-up study of peri-implantitis cases after treatment

Abstract: Peri-implant health may not be easy to establish, especially in cases that develop disease early. Homogenous treatment protocols rather than empirical treatment attempts should be adopted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
84
1
14

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(110 citation statements)
references
References 45 publications
11
84
1
14
Order By: Relevance
“…For details regarding checkerboard DNA-DNA hybridization and culture techniques, see the Appendix and Charalampakis et al (2011).…”
Section: Microbiological Sampling and Analysismentioning
confidence: 99%
“…For details regarding checkerboard DNA-DNA hybridization and culture techniques, see the Appendix and Charalampakis et al (2011).…”
Section: Microbiological Sampling and Analysismentioning
confidence: 99%
“…It is not clear if the microbial composition of a biofilm is affected by the physicochemical properties and texture characteristics of the implant surface. Higher roughness and higher free energy of the implant surface may favour biofilm formation (35), whereas peri-implantitis may occur earlier, with a faster and more extensive progression in implants with rougher surface (36)(37)(38). Nevertheless, it is also shown that abutments with different surface characteristics can influence neither biofilm formation on the implant surface, nor the extent and cellular composition of the resulting inflammatory lesion (39).…”
Section: Such As Staphylococcus Aureus Staphylococcus Epidermidis Ementioning
confidence: 99%
“…Charalampakis, et al evaluated the longevity and incidence of relapse of multiple different treatments on periimplantitis lesions. 107 Over half of the cases evaluated relapsed and were not controlled. Patient habits and early disease development were associated with higher rates of relapse and surgical therapy with lower rates of relapse.…”
Section: Discussionmentioning
confidence: 99%
“…Patient habits and early disease development were associated with higher rates of relapse and surgical therapy with lower rates of relapse. 107 Long-term success of an implant depends on regular maintenance program. During maintenance phase, peri-implant tissue should be evaluated for inflammation.…”
Section: Discussionmentioning
confidence: 99%